Empowerment of Land Resource to Increase Competitiveness and Added Value of Agricultural Product - GITOSUWONDO, SUBOWO (Jurnal Sumberdaya Lahan, 2009)
In global free trade action, Indonesia has many rivalry constrain to involve on standart product quality need which determined by developed countries from subtropical area. Agriculture product added value based on tropical natural resource is not accommodated proportionally, so that the Indonesian farming system has faced many obstacle resulting low competitive. Competitiveness digging of Indonesian specific land resource is a step in the right direction to do, besides it can increase competitiveness and has protected by regionally regulation. The Indonesian spatial competitiveness are sun energy, rainfall, mineral deposit, diversity of agricultural commodities, geographical position, and agricultural land availability for spell of production. Agricultural production arrangement that considering land capacity and specific competitiveness will increase production efficiency, added value, and selling product. Arrangement of spatial plan of various commodities and correct zonation based on need and location of market will increase competitiveness and farmer welfare. Functional food development, commodity choice, harvest area placement and harvest time arrangement are absolute competitiveness of Indonesian agricultural product and can not be competed by other region.